Assessment of a Business Platform for Advancing Corporate Sustainability - Krumpholcová, Sára (2025)
This Master's thesis explores the Změna k lepšímu (ZKL) collaborative sustainability platform by examining the experiences of its member companies. The focus is on collaboration mechanisms, value perception and engagement challenges. Adopting an exploratory qualitative approach, the study combines document analysis with semi-structured interviews and draws on the concepts of stakeholder engagement and collaborative sustainability platforms. Thematic analysis reveals that ZKL effectively fosters networking, resulting in new clients, strategic partnerships and joint sustainability initiatives. Advocacy is also a valued benefit. However, members face capacity constraints and advocate for greater thematic specialisation (e.g., sector-specific working groups) and stronger collaborative support. Suggestions for improvement include proactive matchmaking, targeted legislative monitoring, clearer internal contact points, and better communication flows. To increase ZKL impact, it is recommended to use digital tools, such as an online platform containing databases and forums, as well as more structured in-person formats, such as formal conferences. ZKL is recognised as a connector and amplifier of sustainability efforts, through activities such as knowledge-sharing events, collaborative projects, advocacy initiatives and capacity-building initiatives. The research provides strategic recommendations for ZKL and insights into the experiences of members within such platforms.